THE GEOLOGICAL STRUCTURE OF THE ALLOCHTHONOUS "ATHENS SCHISTS" - Παπανικολάου Δ. I.; Λόζιος Σ. Γ.; Σούκης K. Ι.; Σκούρτσος Εμ. Ν. (Bulletin of the Geological Society of Greece, 2004)
Based on lithological fades, deformation and metamorphic degree the alpine tectonostratigraphic complex known in the literature as "Athens Schists" is divided into two units: the non-metamorphosed overlying Athens Unit and the very low grade metamorphosed underlying Alepovouni Unit. Athens Unit crops out in several hills of the western and central part of the Athens Basin emerging through the post-alpine sediments. It comprises several lithologies that constitute two lithologie groups: the first one of neritic white massive-to thick-bedded carbonates that bear rudist fragments and Upper Cretaceous foraminifera. These limestones are olistholites within the second pelagic formation comprising marly limestones with Globotruncana sp., shales, sandstones, tuffs and ophiolithic blocks. Due to tectonic intercalating of these two lithological groups Athens Unit shows a complex internal structure. It represents an Upper Cretaceous mélange formed in an accretionary prism. Alepovouni Unit is observed at the eastern part of the Athens Basin along the foothills of Mt. Hymettos, wedged between Athens Unit and the metamorphic rocks of Mt. Hymettos. It comprises two lithological groups, in which remnants of Thassic fossils were reported. Alepovouni Unit is correlated to the allochthonous Lavhon Unit that tectonically overlies the autochthonous Attica Unit in SE Attica. At the eastern part of the Athens Basin, Alepovouni Unit is bounded by two west-dipping lowangle normal faults. Along these contacts the formations of both Athens and Alepovouni Units exhibit microstructures indicating top-to NW sense of shear. The contact between the Athens Unit and Alepovouni Unit in western Hymettos is probably a major extensional detachment separating the metamorphic units of Attica autochthon and Alepovouni at the footwall to the SE from the nonmetamorphic units of the Sub-Pelagonian and the Athens unit at the hangingwall to the NW. This major detachment fault accommodated the uplift of the metamorphic rocks and juxtaposed these two units. At the western part Athens Unit overlies tectonically the Paleozoic - Mesozoic formations of the Sub-Pelagonian unit. The contact is an east-dipping normal fault, antithetic to the major detachment of western Hymettos.